Analysis of the Role of Service Innovation and Product Quality in Revitalizing Culinary Business in Malang - Adinugroho, Iwan; Panjaitan, Feliks Anggia Binsar Kristian; Samuddin, Syurwana Farwita; Sutanto, Himawan; Souisa, Wendy (West Science Business and Management, 2024)
This study investigates the role of service innovation and product quality in revitalizing culinary businesses in Malang. Using a quantitative research design, data were collected from 66 culinary business owners and managers through a structured questionnaire, with responses measured on a 5-point Likert scale. The analysis, conducted using SPSS version 25, revealed that both service innovation and product quality significantly contribute to business revitalization, with product quality demonstrating a stronger influence. These findings highlight the importance of integrating innovative service delivery methods with consistent product quality to enhance customer satisfaction and sustain competitiveness. The study offers valuable insights for culinary entrepreneurs and policymakers aiming to foster sustainable growth in Malang's culinary industry.